(untitled) (American Journal of Islam and Society, 2008)
Using the role of an immigrant researcher in her country of origin, Shahnaz Khan uses her feminist lens to explore dualities, decontextualization, and stereotypes of third-world women, more specifically Muslim women, while examining the contested issue of the ZinaOrdinance and itsmultifaceted consequences for women in Pakistan. Juxtaposing her feminist analysis within the context of transnational feminism, the author examines the tensions surrounding this ordinance by questioning three intersecting contexts, namely, culture, politics, and religion. Pointing out such issues as corruption, male violence, poverty, and drug and alcohol abuse, Khan argues that the ordinance allows families, in collaboration with the state, to regulate women’s sexuality. She reminds her readers that women charged with adultery and fornication by the state are not victims, as they resist their incarceration in multiple ways. Ironically, the prisons as well as the state-sponsored shelters become safer spaces for women to flee the wrath of their families ...